The Influence Of Influencer Marketing And Brand Image On Consumer Purchase Decisions For Gadah Fried Chicken With Purchase Interest As A Mediation Variable: A Study on Followers of the Instagram Account @ayamgorenggadah - Meisha Farah Widyaningrum; Rusdi Hidayat Nugroho (LPPM Sekolah Tinggi Ilmu Ekonomi 45 Mataram, 2026)
This study aims to analyze the influence of influencer marketing and brand image on consumer purchasing decisions for Ayam Goreng Gadah, with purchase intention as a mediating variable. The background of this study is based on the rapid development of digital marketing through social media, especially Instagram, which is now one of the main marketing platforms for local culinary businesses. The study uses a causal associative quantitative approach with data collection through a Likert-scale questionnaire to followers of the Instagram account @ayamgorenggadah who have purchased the product. Sampling was determined using a purposive sampling technique using the Slovin formula. Data analysis used the Structural Equation Modeling–Partial Least Squares (SEM-PLS) method with the help of the SmartPLS application. The test results show that all research indicators meet convergent and discriminant validity. The R² value for purchasing decisions is 0.514 (moderate category) and the R² value for purchasing intentions is 0.282 (weak category). Hypothesis testing proves that influencer marketing has a positive and significant effect on purchase intention (β=0.424; p=0.000) and purchase decision (β=0.257; p=0.001). Brand image also has a positive and significant effect on purchase intention (β=0.265; p=0.000) and purchase decision (β=0.220; p=0.002). In addition, purchase intention is proven to mediate the influence of influencer marketing (β=0.194; p=0.001) and brand image (β=0.121; p=0.003) on purchase decision. In conclusion, optimizing influencer marketing strategy and strengthening brand image effectively increases consumer purchase intention, which ultimately drives purchase decisions in local culinary businesses based on social media.